2019
DOI: 10.1645/17-137
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Host Body Size and Food Guild on Prevalence and Mean Intensity of Chewing Lice (Phthiraptera) on Birds in Southern China

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
4
21
1
Order By: Relevance
“…Notably, almost no lice were collected from migrating passerines at Jinshanyakou (one bird; 0.7% infested), whereas 59 of 162 (36%) of the resident passerine birds caught at Ailaoshan were infested with chewing lice (Table 1). This is in contrast with the results reported by Chu et al (2019), who found that there were no significant differences in prevalence between resident and migrant birds in China. Several factors may explain this discrepancy.…”
Section: Impact Of Migrationcontrasting
confidence: 99%
See 3 more Smart Citations
“…Notably, almost no lice were collected from migrating passerines at Jinshanyakou (one bird; 0.7% infested), whereas 59 of 162 (36%) of the resident passerine birds caught at Ailaoshan were infested with chewing lice (Table 1). This is in contrast with the results reported by Chu et al (2019), who found that there were no significant differences in prevalence between resident and migrant birds in China. Several factors may explain this discrepancy.…”
Section: Impact Of Migrationcontrasting
confidence: 99%
“…between regions with different external environments). This hypothesis may explain the differences between the results of the present and those reported by Chu et al (2019) and would be in line with much lower infestation rates in migratory birds caught in Sweden and Japan (D. R. Gustafsson, unpublished data). However, our present data set from Yunnan is not sufficient to test this hypothesis; future collections in China will focus on the difference between SCM and NCM birds, specifically.…”
Section: Impact Of Migrationsupporting
confidence: 82%
See 2 more Smart Citations
“…Body size is one of the most relevant characteristics of host organisms; larger birds tend to harbour more lice in comparison to both within (Galloway and Lamb 2017;Chu et al 2019; but see Darolova et al 2001) and across species (Rózsa 1997;Harnos et al 2017). Larger hosts probably provide more durable 'habitat patches', with larger surface areas, and more diverse sets of topographic refugia (Rózsa 1997;Poulin 2011) for lice.…”
Section: Introductionmentioning
confidence: 99%